Penerapan Tema Simbolis pada Bentuk Rancangan Museum dan Pusat Dokumentasi Perfilman Nusantara di Surabaya - Siti Maria Ulfah; Esty Poedjioetami; Suci Ramadhani (Institut Teknologi Adhi Tama Surabaya, 2021)
Abstract. Films in Indonesia have a long history, and are even now considered an era of national film revival, which is marked by the condition of films experiencing an ever-increasing number of production. Due to the lack of facilities available specifically for archipelago film archives in Indonesia, this background is the reason for the need to build a Museum and Archipelago Film Documentation Center located in Surabaya, where according to the Indonesian Film Agency the island of Java is the region that dominates the largest number of film viewers in Indonesia. The method used in this research is a qualitative method with descriptive research type by making observations, field studies and literature. The land chosen for the designer is located on Jalan Simpang Dukuh, Suarabaya City with an area of 0.76 hectares with a relatively flat site. The use of a symbolic theme with a representative concept was chosen so that the building being designed does not only pay attention to its function. In addition to attracting visitors with the use of symbols in the form of building design, it is hoped that it will be able to appear to show the philosophy and functions that are in it which are used as a means of education, research and entertainment just by looking at the outer appearance of a building.Keywords: Film, Museum, Symbolic. Abstrak. Perfilman di Indonesia memiliki sejarah yang cukup panjang, bahkan sampai saat ini dianggap sebagai era kebangkitan perfilman nasional yang ditandai dengan kondisi perfilman yang mengalami pertumbuhan jumlah produksi yang terus meningkat. Karena minimnya fasilitas yang tersedia khusus arsip film Nusantara di Indonesia, dengan latar belakang tersebut menjadi alasan perlu dibangunnya sebuah Museum dan Pusat Dokumentasi Perfilman Nusantara yang terletak di Surabaya, dimana menurut Badan Perfilman Indonesia pulau Jawa merupakan wilayah yang mendominasi jumlah penonton film terbanyak di Indonesia. Metode yang digunakan dalam penelitian adalah metode kualitatif dengan jenis penelitian deskriptif dengan melakukan observasi, studi lapangan dan literatur. Penggunaan tema simbolis dengan konsep representatif dipilih agar bangunan yang didesain tidak hanya memperhatikan fungsinya. Selain untuk menarik pengunjung dengan penggunaan simbolieme pada bentuk desain bangunan diharapkan mampu tampil menunjukkan filosofi dan fungsi yang ada didalamnya yang tidak lain digunakan sebagai sarana edukasi, penelitian maupun hiburan hanya dengan melihat tampilan luar dari suatu bangunan.Kata Kunci: Film, Museum, Simbolis.